METHODS OF VOCAL AND CHORAL WORK WITH STUDENTS IN MUSIC LESSONS (Pedagogy of Higher and Secondary Education, 2004)
On a present day stage of development of musical pedagogics the problem of forming of vocal-choral skills in the  process of pupils’ education is the most actual. The vocal-choral singing takes a special place in the aesthetical and artistic pupils' upbringing.